Sepsis-Associated Encephalopathy (Review) - N. B. Beloborodova; I. V. Ostrova (Общая реаниматология, 2018)
International studies demonstrate an annual increase in the frequency and impact of sepsis in intensive care units (ICU). Cerebral dysfunction, or so-called sepsis-associated encephalopathy (SAE), is one of the earliest signs of sepsis, as well as its common complication. Up to 70% of patients with sepsis have symptoms of encephalopathy [1, 2]. A direct link between the SAE and an increased mortality rate is a major concern; more than a half of sepsis survivors experience continuous memory and concentration impairment [3—5]. Diagnosis of the cerebral dysfunction in sepsis is often difficult because of lack of specific biomarkers and frequent prescription of sedatives to critically ill patients. Clinical manifestations of SAE are diverse, may vary from simple malaise and lack of concentration to deep coma. The literature discusses probable mechanisms of formation and development of septic encephalopathy, such as oxidative stress, inflammation, mitochondrial and endothelial dysfunction, increased permeability of the blood-brain barrier, impairment of macro- and microcirculation, changes in neirotransmission, activation of microglia. The lack of clear data and consensus about the etiology and mechanisms of SAE at present does not permit predicting its development and prescribing a specific therapy. The review discusses current understanding of the causes of septic encephalopathy, methods of diagnosis, the main clinical manifestations, key mediators, and pathophysiological mechanisms. A hypothesis is proposed that poses a contribution of aromatic microbial metabolites (AMM) of phenol and indole nature (products of bacterial biodegradation of tyrosine and tryptophan) to the development of brain dysfunction. The fields of exploratory studies, which might open perspectives in the diagnosis, as well as new approaches in the treatment of SAE are outlined.